2020
DOI: 10.24925/turjaf.v8i5.1039-1042.3164
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Canopy Area of Fruit Trees Using Light Unmanned Aerial Vehicle (UAV) and Image Processing Methods

Abstract: Some vegetative properties measured in fruit trees are important indicators in examining of plant growth calculation, estimation of leaf area index in evapotranspiration, fertilizer requirement etc. These measurements reflect the effects of the cultivation treatments in many areas of commercial growing and scientific studies. One of the most important measurements is the status of the canopy development. Canopy width, area and volume can be measured with some calculations. However, more technological equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The 𝜒, 𝛿 calculated using the two represent the accuracy and recall of the calculated results [23]. These two parameters can to some extent reflect the target detection ability of CBAMYOLOv5-CNN in ARSIs, but their shortcomings lie in not considering the impact of mean accuracy [24]. For this issue, the study uses Eq.…”
Section: Fig 5 Screening Process Of Redundant Information In Convolut...mentioning
confidence: 99%
“…The 𝜒, 𝛿 calculated using the two represent the accuracy and recall of the calculated results [23]. These two parameters can to some extent reflect the target detection ability of CBAMYOLOv5-CNN in ARSIs, but their shortcomings lie in not considering the impact of mean accuracy [24]. For this issue, the study uses Eq.…”
Section: Fig 5 Screening Process Of Redundant Information In Convolut...mentioning
confidence: 99%
“…When focusing on RGB images, a large number of studies of tree phenotype in orchards can be found. Using image processing techniques, Yıldız et al (2020) determined the canopy area of apple trees. Regression analysis employed both circular and elliptical calculating techniques.…”
Section: Introductionmentioning
confidence: 99%